A case report of fulminant cytokine release syndrome complicated by dermatomyositis after the combination therapy with immune checkpoint inhibitors. Issue 15 (April 2020) - Ohira, Junichiro; Kawamoto, Michi; Sugino, Yoshio; Kohara, Nobuo
Abstract: Introduction: Immune-related adverse events (ir-AEs) are increasingly becoming a concern, as immune checkpoint inhibitors (ICIs) are used more frequently. Herein, we present a case of fulminant cytokine release syndrome (CRS) complicated by dermatomyositis after the combination therapy with ICIs. Patient concerns: A 70-year-old male developed dermatomyositis during the course of treatment with two ICIs, nivolumab and ipilimumab. He was treated by steroid pulse therapy, but the effect was limited. Afterwards, he had acute-onset high fever, hypotension, respiratory failure, impaired consciousness, renal failure, and coagulation abnormality at the same time. C reactive protein (CRP), creatinine kinase (CK), D-dimer, and ferritin levels were considerably elevated: CRP, 24 mg/dL; CK, 40, 500 U/L; D-dimer, 290 μg/mL; ferritin, 329, 000 ng/mL. Diagnosis: CRS induced by ICI combination therapy. Interventions: Given that high fever and elevated CRP level indicated potential sepsis, an antibiotic was used until the confirmation of negative blood cultures. All the simultaneous acute symptoms were supposed to be CRS. He was admitted to the intensive care unit (ICU), and temporary intubation and hemodialysis were needed. Immunosuppressive therapy was reinforced by mycophenolate mofetil together with steroid, and plasma exchange was performed for the elimination of abnormal proteins. Outcomes: The patient's clinical symptoms and laboratory parameters gradually improved and he was discharged from the ICU in a month. Conclusion: Fulminant CRS can be induced by ICI combination therapy. As the initial symptoms of CRS resemble sepsis, it is important to consider CRS as a differential diagnosis and to initiate immunosuppressive therapy early when needed. In steroid-resistant cases, early introduction of other immunosuppressive therapy and plasma exchange can be effective.